Предмет: Математика,
автор: Элой1
Решите уравнение: 4-2(3-2х)=-5-2х
Ответы
Автор ответа:
2
4-2 (3-2х)= -5-2х
4-6+4х= -5-2х
4х+2х= -5-4+6
6х= -3
х= -0,5
Ответ: - 0,5
4-6+4х= -5-2х
4х+2х= -5-4+6
6х= -3
х= -0,5
Ответ: - 0,5
kot7895:
4x+2x=6x, разве нет?
Автор ответа:
1
4-2(3-2х)=-5-2х
4-6+4x=-5-2x
4-6+4x+5+2x=0
6x+3=0
x=2
можно еще так решить:
4-2(3-2х)=-5-2х
4-6+4x=-5-2x
4x+2x=-5-4+6
6x=-3
6x+3=0
x=2
4-6+4x=-5-2x
4-6+4x+5+2x=0
6x+3=0
x=2
можно еще так решить:
4-2(3-2х)=-5-2х
4-6+4x=-5-2x
4x+2x=-5-4+6
6x=-3
6x+3=0
x=2
Похожие вопросы
Предмет: Литература,
автор: Аноним
Предмет: Информатика,
автор: janbo9358
Предмет: Математика,
автор: loikasoev3864
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: Juli0000